2018
DOI: 10.1002/pd.5197
|View full text |Cite
|
Sign up to set email alerts
|

Delivering an accredited non‐invasive prenatal diagnosis service for monogenic disorders and recommendations for best practice

Abstract: The identification of cell-free fetal DNA circulating in maternal blood combined with technological developments, in particular next-generation sequencing, is enabling the development of safer prenatal diagnosis. While this technology has been widely applied as a highly sensitive screening test for aneuploidy, there has been relatively little clinical application for the diagnosis of monogenic disorders. In the UK, we have established non-invasive prenatal diagnosis (NIPD) as a clinical service for a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 41 publications
(57 reference statements)
0
69
0
2
Order By: Relevance
“…24 Moreover, prenatal mutation characterization might be helpful in identifying mutations strongly associated with a poor prognosis. This may be possible using non-invasive prenatal diagnosis as has been reported in other FGFR2 craniosynostosis syndromes 34 or, if invasive testing is acceptable, using a targeted exome sequencing approach 35 In difficult cases of fetal abnormalities suggesting an acrocephalosyndactily syndrome, less invasive autopsy may be an alternative to guide the molecular analysis when parents do not consent to traditional autopsy. 36 In our study, post-mortem radiographs, MRI, and CT demonstrated the additional abnormalities: binucleated vertebral bodies, vertebral posterior arch fusion, sacral appendage, and cartilaginous tracheal sleeve.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…24 Moreover, prenatal mutation characterization might be helpful in identifying mutations strongly associated with a poor prognosis. This may be possible using non-invasive prenatal diagnosis as has been reported in other FGFR2 craniosynostosis syndromes 34 or, if invasive testing is acceptable, using a targeted exome sequencing approach 35 In difficult cases of fetal abnormalities suggesting an acrocephalosyndactily syndrome, less invasive autopsy may be an alternative to guide the molecular analysis when parents do not consent to traditional autopsy. 36 In our study, post-mortem radiographs, MRI, and CT demonstrated the additional abnormalities: binucleated vertebral bodies, vertebral posterior arch fusion, sacral appendage, and cartilaginous tracheal sleeve.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…This further emphasises the need to involve the clinical geneticist in the prenatal evaluation of these conditions. For achondroplasia, thanatophoric dysplasia, and Apert syndrome, as well as selected other syndromes, definitive molecular diagnosis can be achieved using NIPD and analysis of cell‐free DNA in maternal blood . Of greater potential utility, but requiring invasive testing, is exome sequencing, which has the ability to screen affected pregnancies for multiple mutations in many genes, thereby increasing the possibility of arriving at a definitive diagnosis in a timely fashion in pregnancy.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…39 Both 2D and 3D ultrasonography have limitations in the presence of a high maternal body mass index, excessive fetal movements and thoracic shadowing, particularly at later gestational ages. These limitations can to some extent be [44][45][46] Of greater potential utility, but requiring invasive testing, is exome sequencing, which has the ability to screen affected pregnancies for multiple mutations in many genes, 47 thereby increasing the possibility of arriving at a definitive diagnosis in a timely fashion in pregnancy. Exome sequencing with variant interpretation focused on a virtual panel of genes known to cause skeletal dysplasias has been shown to have a diagnostic yield as high as 83% in fetuses suspected of having a skeletal dyplasia.…”
Section: Other Imaging Aids To Sonographic Diagnosis Of Skeletal Dymentioning
confidence: 99%
“…Cff‐DNA in maternal plasma contains the complete fetal profile; therefore, theoretically, NIPT could be applied to all monogenic disorders . The increasing availability and accessibility of next‐generation sequencing (NGS) has enabled the development of NIPT for single‐gene disorders, including the complicated conditions of autosomal recessive or X‐linked disorders, since the majority of cell‐free DNA is of maternal origin …”
Section: Introductionmentioning
confidence: 99%
“…7 The increasing availability and accessibility of next-generation sequencing (NGS) has enabled the development of NIPT for single-gene disorders, including the complicated conditions of autosomal recessive or X-linked disorders, since the majority of cell-free DNA is of maternal origin. 8,9 The de novo pattern and hotspot mutation of ACH and TD make them ideal candidates for NIPT. The successful detection of fetal ACH or TD mutation in the maternal plasma using different approaches had already been reported, including PCR-RED, high-resolution melting, MALDI-TOF, droplet digital PCR and minisequencing.…”
Section: Introductionmentioning
confidence: 99%